Serratia marcescens Infectious Endocarditis: Injection Drug Use, Left-Sided Heart Disease, and Poor Outcomes. Issue 4 (July 2018) - Schechter, Marcos C.; Spicer, Jennifer O.; del Mar Aldrete, Sol; Kraft, Colleen S.
Abstract : Background: Serratia marcescens infectious endocarditis (SMIE) is an uncommon disease, and the largest case series were reported from California in the 1970s. We aimed to identify risk factors and outcomes of SMIE in our institution. Methods: Retrospective cohort study of all cases of Serratia marcescens bacteremia (SMB) diagnosed between January 2003 and December 2013. Results: A total of 298 cases of SMB were reviewed, and 5 cases of SMIE were found. Clinical characteristics between SMB and SMIE cases were similar, except for more frequent history of injection drug use among cases of SMIE. Serratia marcescens infectious endocarditis cases had large vegetations, frequent embolic events, and poor outcomes. Conclusions: We confirm the stereotypical description of SMIE as a cause left-sided heart disease in injection drug users with frequent embolic events. Poor outcomes prevailed despite advances in medical care. Abstract : Serratia marcescens is a rare of cause of endocarditis. The authors reviewed all cases of S. marcescens bacteremia (SMB) at their institution between 2003–2013 and aimed to identify risk factors and outcomes of endocarditis. SMB cases with and without endocarditis were similar, except for more frequent history of injection drug use among those with endocarditis. Endocarditis cases had large vegetations, frequent embolic events, and poor outcomes.